Lamotrigine for pediatric patients with epilepsy. Issue 2 (April 2008) - Biton, Victor
The antiepileptic drug lamotrigine has been assessed in various seizure types and epilepsy syndromes in children and is indicated in the USA and other countries for adjunctive treatment of epilepsy in patients as young as 2 years. This paper reviews data on the pharmacokinetics, efficacy and safety of lamotrigine in pediatric patients. Data from clinical trials and experience in clinical practice demonstrate that lamotrigine is effective for a range of seizure types, including generalized seizures (including absence) and partial seizures. Observations primarily from open-label studies are consistent with the possibility that lamotrigine is effective in several pediatric epilepsy syndromes, including infantile spasms and juvenile myoclonic epilepsy as well as Rett''s syndrome, a neurogenetic disorder that is often associated with epilepsy. The safety and tolerability profiles of lamotrigine in pediatric patients are consistent with those in adults. The risk of rash with lamotrigine can be reduced by adhering to current dosing recommendations. Lamotrigine-associated improvements in mood, cognition and behavior could be particularly useful in pediatric patients given the high rate of behavioral and mental abnormalities in children with epilepsy. Randomized, double-blind, placebo-controlled studies on the effects of lamotrigine on mood, cognition and behavior in pediatric patients are warranted. The safety and efficacy of lamotrigine as monotherapy in pediatric patients also warrant further investigation.